DENTAL PROSTHETICS ON IMPLANTS AND THEIR FEATURES - Ахмедов Алишер Астанович; Нарзиева Нигора (American Journals, 2023)
The functionality and aesthetics of implant-based bridges are ensured by the inclusion of teeth adjacent to the defect in the prosthetic structure. Against the background of reproductive periodontitis, the connection of healthy teeth and implants with the help of multicomponent orthopedic structures stabilizes the dentition and prevents the exacerbation of inflammatory-destructive processes in periodontal tissues. Use of materials for implants with important bone-like properties deformation properties, reduces the occurrence of stress zones at the bone-implant interface. Vestibular and intraoral displacement of implants in patients with malocclusion increases resistance to masticatory lateral loading.
Keywords: Atrophy of the alveolar ridge, fixed and removable dentures.